Dětská delikvence (aktuální právní a psychologické otázky) - Čechová, Soňa (2006)
Résumé Childrens delinquency is the most serious socially pathological phenomenon, with a number of qualities different from the criminality committed by adults. The characteristic features of childrens criminality are determined by their age, i.e. mental and somatic development, features of character and experience. Delinquency among children-offenders is conditioned by a number of factors. These and many other topics are dealt with in the thesis entitled: Childrens Delinquency (Topical Legal and Psychological Aspects). In accordance with the diploma thesis concept, the paper has been divided into a theoretical and a practical part. The objective of the first chapter of the theoretical part is to provide definitions of delinquency and criminality, followed by the definitions of a child, juvenile, youth and young adult, important for further understanding of the text.